Esoteric Symbolism of The Letter Alif in Sosrokartono's Calligraphy and Al-Jilli's Insan Kamil Concept - Irawan, Aguk (DINIKA : Academic Journal of Islamic Studies, 2021)
The study examines the symbolic meaning of the letter Alif and the esoterism teaching in it, as reflected in Sosrokartono’s calligraphy and Insan al-Kamil’s concept of Al-Jilli.  The purpose of this study is to present the philosophical similarities and differences between the Middle Eastern Sufis and the Indonesian Sufis, which are found in different mediums. The study used library research and hermeneutical approach. The data were analysed using text interpretation from Jorge Garcia and esoteric symbolism from Ferdinand de Saussure. The findings of this study include: first, the letter Alif in the calligraphy holds the meaning of philosophical sufism that aligns with the concept of Insan Al-Kamil by Abdul Karim Al-Jilli. Second, the letter Alif for both Sosrokartono and Al-Jilli holds three dimensional meanings; oneness, strength, and wisdom. This research enriches the repertoire of philosophical Sufism by presenting the meaning of material objects in the form of calligraphy art.